Intelligent planning for large‐scale multi‐agent systems. Issue 4 (11th December 2022) - Ma, Hang
Abstract: This article summarizes the New Faculty Highlights talk with the same title at AAAI 2021. Intelligent agents such as different types of robots will soon become an integral part of our daily lives. In real‐world multi‐agent systems, the most fundamental challenges are assigning tasks to multiple agents (task‐level coordination problems) and planning collision‐free paths for the agents to task locations (motion‐level coordination problems). This article surveys four directions of our research on using intelligent planning techniques for the above multi‐agent coordination problems. Link to video abstract: https://youtu.be/HDAFcatq9_I